Proceedings of the 11th International Congress on the Archaeology of the Ancient Near East Vol. 1: Mobility in the Ancient Near East. Images in Context. Archaeology as Cultural Heritage. Engendering Near Eastern Archaeology. Societal Contexts of Religion. Shaping the Living Space - Otto, Adelheid; Herles, Michael; Kaniuth, Kai (Harrassowitz Verlag, 2020)
The two volumes include 96 selected lectures presented at the "11th International Congress on the Archaeology of the Ancient Near East" (ICAANE) at LMU München in April 2018. This congress takes place every other year and is the platform for all archaeologists worldwide to present the current results of their research in and on the Near East. The timeframe comprises the Prehistoric Period, the Bronze and Iron Ages as well as the Islamic Period; the geographical frame spans the area from Western Turkey to Afghanistan, and from Georgia to Yemen. Since researchers come from 35 countries, they summarize their latest discoveries mostly in English. The ICAANE proceedings give a state of the art-insight into current research methods and problems of Near Eastern Archaeology. Volume 1, edited by Adelheid Otto, Michael Herles and Kai Kaniuth, comprises c. 40 contributions related to the conference themes of Mobility in the Ancient Near East, Images in Context, Engendering Near Eastern Archaeology, Societal Contexts of Religion, Shaping the Living Space and Archaeology as Cultural Heritage.